Penguatan Kapasitas Kelembagaan dan Dampaknya Terhadap Efektivitas Pelayanan Kesehatan Hewan - Titik Herawati; Rita Rahmawati; Oetje Subgdja (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The purpose of this research is to determine the influence of institutional capacity strengthening and its impact on the effectiveness of animal health services. This research uses a quantitative approach, which is a post-positivist research method employed to study a specific population or sample. Data collection is done using research instruments, and data analysis is statistical in nature with the aim of testing established hypotheses, thereby identifying the variables that influence and are influenced by them. The total number of respondents included in this study was 31 individuals. Several data collection techniques were used, including questionnaires, observation, literature review, documentation, and interviews. Data analysis was conducted using Likert scales and regression analysis through the SPSS program. The research results indicate that individual capacity strengthening has a negative impact on the effectiveness of animal health services, organizational capacity strengthening has a negative impact on the effectiveness of animal health services, system capacity strengthening has a negative impact on the effectiveness of animal health services, and institutional capacity strengthening has a positive impact on the effectiveness of animal health services.